PENGARUH KESEIMBANGAN KEHIDUPAN KERJA, STRES KERJA , DAN KETERLIBATAN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA PT. NUSANTARA SAKTI GROUP CABANG BOJA) - Barita Santoso Pakaya; Hasan Abdul Rozak (ITB AAS Indonesia Surakarta, 2025)
Finding out how work-life balance, stress, and engagement affect employee performance at PT. Nusantara Sakti Group, Boja Branch, is the goal of this study. In this investigation, quantitative approaches were applied. At PT. Nusantara Sakti Group, Boja Branch, there were 35 employees in total, including a sample of 35 employees. This study's data was gathered using a questionnaire with a Likert scale ranging from 1 to 5. The SPSS 2021 program was used to examine the data. The study's findings suggest that work-life balance, job stress, and work engagement all significantly and favorably impact employee performance. Employee performance is positively and significantly impacted by work-life balance, positively and significantly impacted by work stress, and unaffected by work engagement. Keywords: Work-Life Balance, Work Stress, Work Engagement, Employee Performance